Phase 3, open‐label, randomized study of the pharmacokinetics, efficacy and safety of ixekizumab following subcutaneous administration using a prefilled syringe or an autoinjector in patients with moderate‐to‐severe plaque psoriasis (UNCOVER‐A). (8th August 2016) - Callis Duffin, K.; Bagel, J.; Bukhalo, M.; Mercado Clement, I.J.; Choi, S.L.; Zhao, F.; Gill, A.; Pangallo, B.; Shuler, C.; Mallbris, L.; Jackson, K.
Abstract: Background: The efficacy of ixekizumab, an anti‐interleukin‐17A (anti‐IL‐17A) monoclonal IgG4 antibody, was demonstrated in moderate‐to‐severe psoriasis patients when administered via prefilled syringe (PFS). Objective: To evaluate the effect of two drug delivery devices on the pharmacokinetics (PK) of ixekizumab as well as efficacy and safety with both devices. Methods: In the first 12 weeks of an open‐label, phase 3 study, moderate‐to‐severe psoriasis patients were randomized to ixekizumab delivery via PFS or autoinjector device. Randomization was stratified by weight (<80 kg, 80–100 kg, >100 kg), injection assistance (yes/no) and injection site (arm, thigh or abdomen). Following a 160‐mg initial dose at week 0, patients received subcutaneous 80‐mg ixekizumab as a single injection every 2 weeks for 12 weeks. Blood samples were collected following the initial 160‐mg dose on days 2, 4, 7, 10 and 14 for PK analysis. Primary PK parameters were maximum concentration ( C max ) and area under the curve (AUC0‐tlast ) where t last is the time of last sample (14 days ± 24 h). Efficacy was assessed by percent improvement on the Psoriasis Area and Severity Index (PASI) at week 12. Adverse event reporting, vital signs and clinical laboratory data were used to evaluate safety. Results: Of 204 randomized patients, 192 were included in the PK analysis (PFS: 94; autoinjector: 98). The PFS and autoinjector showed similar geometric mean C max (90% CI) [15.0 μg/mL (13.9–16.1) vs. 14.8 μg/mL (13.8–15.9)] and geometric mean AUC0‐tlast (90% CI) [157 μg × day/mL (147–168) vs. 154 μg × day/mL (144–165)]. When comparing C max and AUC0‐tlast of the autoinjector to PFS, the geometric LS mean ratios were 0.97. At week 12, mean percent PASI improvement (via modified baseline observation carried forward) was similar with the PFS (89.3%) and autoinjector (86.9%). Both devices had safety results that were consistent with the known safety profile of ixekizumab. Conclusion: The PK, efficacy and safety of ixekizumab administered subcutaneously by PFS and autoinjector were similar. Clinicaltrials.gov number: NCT01777191https://clinicaltrials.gov/ct2/show/NCT01777191